Cardiac screening in swimming - Riding, N. (FINA World Sports Medicine Congress, 18, 2016)
Dr. Nathan Riding (ASPETAR, QAT) talks about "Cardiac Screening in Swimming" at the FINA World Sports Medicine Congress 2016 (18:59 min).